Digitalisasi Data Usaha Melalui Profiling Data Statistical Business Register (SBR) dan Tagging Usaha Berbasis SW Maps di BPS Kabupaten Sidoarjo - Yumna Almas Elsaviyanto; Alshaf Pebrianggara (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2026)
Digital transformation in the field of statistics requires the availability of business data that is highly accurate, constantly updated, and systematically integrated. In this regard, the Central Statistics Agency (BPS) plays an important role in maintaining data quality through the updating of the Statistical Business Register (SBR). This study aims to describe the implementation of business data digitization through SBR profiling and business tagging based on the SW Maps application at the BPS in Sidoarjo Regency, using a qualitative descriptive approach in the form of a case study conducted during an internship program. The findings indicate that the business data digitization process was carried out in stages and interconnected, starting with the use of Microsoft Excel for data pre-processing, followed by MatchaPro for SBR updating and validation, and SW Maps for determining business locations based on geographic coordinates. Profiling activities play a role in maintaining the consistency and validity of business data, while the tagging process serves to complement non-spatial data with spatial information. However, during implementation, several technical challenges were encountered, including inaccurate coordinates, data entry errors, network connectivity disruptions, and limited access via Virtual Private Network (VPN). Overall, the integration of SBR profiling and SW Maps-based business tagging activities has proven effective in improving the quality of business data management and supporting the provision of more accurate, reliable, and sustainable regional economic statistics.